Effects of Active Hexose Correlated Compound on the Seasonal Variations of Immune Competence in Healthy Subjects. (January 2015) - Takanari, Jun; Hirayama, Yosuke; Homma, Kohei; Miura, Takehito; Nishioka, Hiroshi; Maeda, Takahiro
The aim of this study was to evaluate the effects of active hexose correlated compound intake on the immune competence in healthy volunteers. Thirty-four subjects were randomized to receive placebo or active hexose correlated compound at 1.0 g/d for 4 weeks in early winter. Natural killer cell activity was significantly increased in both groups during the study period, the natural killer cell number, however, was not altered in the active hexose correlated compound group while placebo group showed remarkable decline. In addition, the score of immunological vigor, an index of total immune competence, was maintained in the active hexose correlated compound group although that of placebo group lowered during the test period. These results suggested that the continuous active hexose correlated compound intake maintained the immune competence against the seasonal change.